Targeted Genomic Profiling Reveals Recurrent KRAS Mutations in Mesonephric-like Adenocarcinomas of the Female Genital Tract. (February 2018) - Mirkovic, Jelena; McFarland, Marie; Garcia, Elizabeth; Sholl, Lynette M.; Lindeman, Neal; MacConaill, Laura; Dong, Fei; Hirsch, Michelle; Nucci, Marisa R.; Quick, Charles M.; Crum, Christopher P.; McCluggage, W. Glenn; et al.
Abstract : Mesonephric adenocarcinoma most commonly arises in the cervix and is presumed to be derived from normal or hyperplastic mesonephric remnants. It is characterized by recurrent KRAS mutations and lack of PIK3CA / PTEN alterations. Adenocarcinomas of the uterine corpus and ovary characterized by morphologic and immunophenotypic similarities to mesonephric adenocarcinoma have been reported. The pathogenesis of these tumors, which have been designated "mesonephric-like adenocarcinomas" is unknown, and it has been debated whether these represent mesonephric adenocarcinomas that arise in the endometrium/ovary or endometrioid adenocarcinomas that closely mimic mesonephric adenocarcinoma. The relationship at the molecular level between mesonephric adenocarcinomas and mesonephric-like adenocarcinomas is unknown. The aim of this study was to examine the molecular alterations in mesonephric-like adenocarcinomas to identify driver mutations and potential therapeutically targetable mutations, and to determine the relationship between mesonephric-like adenocarcinomas and mesonephric adenocarcinomas using targeted next-generation sequencing. Seven mesonephric-like adenocarcinomas (4 ovarian, 3 uterine corpus) underwent targeted next-generation sequencing to detect mutations, copy number variations and structural variants in exonic regions of 300 cancer genes, and 113 selected intronic regions across 35 genes. All 7 tumors (100%) harbored canonical activating KRAS mutations (4 G12D, 3 G12V). PIK3CA activating mutations were identified in 3 of 7 (43%) cases. There were no alterations in PTEN, ARID1A, or TP53 in any of the tumors. In copy number analysis, 5 of 7 (71%) tumors exhibited 1q gain, which was accompanied by 1p loss in 2 cases. In addition, 4 of 7 (57%) tumors had chromosome 10 gain, which was accompanied by gain of chromosome 12 in 3 cases. Mesonephric-like adenocarcinomas, similar to mesonephric adenocarcinomas, are characterized by recurrent KRAS mutations, gain of 1q, lack of PTEN mutations, and gains of chromosomes 10 and 12. PIK3CA mutations, which have not previously been identified in mesonephric adenocarcinoma, were found in 3 of 7 (43%) mesonephric-like adenocarcinomas in our study. Mesonephric-like adenocarcinomas exhibit strikingly similar molecular aberrations to mesonephric adenocarcinomas, but also frequently harbor PIK3CA mutations, demonstrating biological overlap with carcinomas of both mesonephric and Mullerian (endometrioid) differentiation. Given the previously documented association with endometriosis (ovarian neoplasms) and the prominent endometrial involvement (uterine corpus neoplasms), we believe these are best regarded as of Mullerian origin and representing adenocarcinomas which differentiate along mesonephric lines; as such, we propose the term mesonephric-like Mullerian adenocarcinoma. Abstract : Supplemental Digital Content is available in the text.